2018
DOI: 10.1029/2018gl078524
|View full text |Cite
|
Sign up to set email alerts
|

Observations and Modeling of the Mars Low‐Altitude Ionospheric Response to the 10 September 2017 X‐Class Solar Flare

Abstract: Solar extreme ultraviolet and X‐ray photons are the main sources of ionization in the Martian ionosphere and can be enhanced significantly during a solar flare. On 10 September 2017, the Mars Atmosphere and Volatile EvolutioN orbiter observed an X8.2 solar flare, the largest it has encountered to date. Here we investigate the ionospheric response before, during, and after this event with the SuperThermal Electron Transport model. We find good agreement between modeled and measured photoelectron spectra. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 55 publications
4
40
0
Order By: Relevance
“…(2) When the foot point(s) of a field line is embedded in the dayside ionosphere, ionospheric photoelectrons can be observed in the field‐aligned direction(s) (e.g., Xu, Mitchell, Liemohn, et al, ; Xu, Mitchell, Luhmann, et al, ; Xu, Mitchell, et al, ). Martian ionospheric photoelectrons can be identified through typical spectral features (e.g., Coates et al, ; Frahm et al, ; Liemohn et al, ; Mitchell et al, ; Peterson et al, ; Xu, Thiemann, et al, ): a cluster of peaks from 22 to 27 eV from the 30.4 nm He‐II solar line ionizing CO 2 and O, a sharp flux drop from 60 to 70 eV (termed “the photoelectron knee”), corresponding to a sharp decrease of solar irradiance at wavelengths shorter than 17 nm, and also the large flux decrease near 500 eV as the source term is extremely small for wavelengths <∼1 nm. Similarly, photoelectrons seen in one or both field‐aligned directions indicate an open or closed field line, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…(2) When the foot point(s) of a field line is embedded in the dayside ionosphere, ionospheric photoelectrons can be observed in the field‐aligned direction(s) (e.g., Xu, Mitchell, Liemohn, et al, ; Xu, Mitchell, Luhmann, et al, ; Xu, Mitchell, et al, ). Martian ionospheric photoelectrons can be identified through typical spectral features (e.g., Coates et al, ; Frahm et al, ; Liemohn et al, ; Mitchell et al, ; Peterson et al, ; Xu, Thiemann, et al, ): a cluster of peaks from 22 to 27 eV from the 30.4 nm He‐II solar line ionizing CO 2 and O, a sharp flux drop from 60 to 70 eV (termed “the photoelectron knee”), corresponding to a sharp decrease of solar irradiance at wavelengths shorter than 17 nm, and also the large flux decrease near 500 eV as the source term is extremely small for wavelengths <∼1 nm. Similarly, photoelectrons seen in one or both field‐aligned directions indicate an open or closed field line, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Xu, Thiemann, et al () investigated the low‐altitude ionospheric response to the X8.2 flare by SuperThermal Electron Transport (STET) model to simulate the photoelectron spectra and ion production rates and densities for periods before the flare, during the flare peak, and during the first MAVEN in situ observations of the period after the flare peak. A good agreement was found between the modeled photoelectron spectra and observations.…”
Section: Heating Of Mars' Atmosphere By the Flare Photonsmentioning
confidence: 99%
“…In terms of compositional changes in the ionosphere, Thiemann et al (2018) reported an increase in the production of O and thus an increase in the relative abundance of O at a fixed pressure, which has implications for photochemical escape (section 6). Xu, Thiemann, et al (2018) investigated the low-altitude ionospheric response to the X8.2 flare by SuperThermal Electron Transport (STET) model to simulate the photoelectron spectra and ion production rates and densities for periods before the flare, during the flare peak, and during the first MAVEN in situ observations of the period after the flare peak. A good agreement was found between the modeled photoelectron spectra and observations.…”
Section: 1029/2018gl079162mentioning
confidence: 99%
“…On the dayside, the Martian ionosphere contains a well-defined primary layer and a low-altitude secondary layer which are mainly produced by solar Extreme Ultraviolet (EUV)/X-ray ionization along with impact ionization by photoelectrons and their secondaries (e.g., Fox & Weber, 2012;Fox & Yeager, 2006, 2009Martinis et al, 2003;Xu et al, 2018). Near the primary peak, the Martian ionosphere is reasonably described by the idealistic Chapman theory under photochemical equilibrium (e.g., Mendillo et al, 2013Mendillo et al, , 2015Mendillo et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%